Influence of non-genetic factors on first lactation and lifetime performance traits in Nili-Ravi buffaloes - Tamboli, Pooja; Bharadwaj, Anurag; Chaurasiya, Amit Kumar; Jan, Mustafa H.; Kumar, Sanjay; Khanna, Sudhir (Frontiers in Animal Science, 2023)
The objective of this research was to evaluate the effects of various non-genetic factors on first lactation and lifetime productivity in Nili-Ravi buffaloes, including season of birth, period of birth, age at first calving, season of first calving, period of first calving, and number of lactations completed. The livestock data on first lactation and lifetime performance traits relevant to 501 Nili-Ravi buffaloes were collected from the history sheet of the animal for a period from 1983 to 2017 (i.e., 35 years) and maintained at the Indian Council of Agricultural Research—Central Institute for Research on Buffaloes (ICAR-CIRB) sub-campus, in Nabha, Punjab, India. To evaluate the least-squares means (LSMs) and the effect of non-genetic factors on performance traits, a least-squares analysis model was applied. The overall LSM for age at first calving (AFC) was 45.03 ± 0.40 months and ranged from 34 to 54 months. The results indicated that the effect of AFC was highly significant (p ≤ 0.01) on first lactation total milk yield (FLTMY), first lactation standard milk yield (305 days or less) (FLSMY), first peak milk yield (FPY), and first lactation length (FLL) in the Nili-Ravi breed of buffaloes. FLTMY, FLSMY, and FPY were highest (2,250.08 ± 48.16 kg, 1,944.68 ± 31.20 kg, and 9.32 ± 0.16 kg/day, respectively) for animals with an AFC of 42–48 months. Furthermore, FLTMY, FLSMY, and FLL were highest (2,411.02 ± 68.68 kg, 2,008.81 ± 44.49 kg, and 357.43 ± 8.13 days, respectively) in animals that first calved in the autumn season. However, the lowest first dry period (FDP), first service period (FSP), and first calving interval (FCI) (110.63 ± 7.42 days, 125.48 ± 9.04 days, and 443.63 ± 9.00 days, respectively) were found for animals that first calved in the rainy season. The overall LSM for herd life (HL), productive life (PL), productive days (PDs), unproductive days (UDs), total lifetime milk yield (total LTMY), standard lifetime milk yield (standard LTMY), milk yield per day of productive life (MY/PL), milk yield per day of productive days (MY/PDs), and milk yield per day of herd life (MY/HL) were estimated as 3,779.84 ± 31.86 days, 2,078.55 ± 24.32 days, 1,552.74 ± 20.06 days, 525.81 ± 12.44 days, 10,229.71 ± 195.31 kg, 9,203.64 ± 173.52 kg, 4.86 ± 0.08 kg/day, 6.46 ± 0.08 kg/day, and 2.66 ± 0.04 kg/day, respectively. The effect of AFC on HL, PDs, UDs, total LTMY, and standard LTMY was highly significant (p ≤ 0.01). Furthermore, the effect of season of first calving on HL, PL, and PDs was significant (p ≤ 0.05). In addition, the effect of the period of first calving on HL, PDs, standard LTMY, and total LTMY was significant (p ≤ 0.05). In these contexts, it can be concluded that the buffaloes of the Nili-Ravi breed with an AFC of 42–48 months performed better than animals with a later AFC in terms of production, reproduction, and lifetime traits.